Optimal Design of Surface Relief Grating for High‐Resolution Two‐Photon Interference Lithography. Issue 6 (31st March 2022) - Ahn, Jinseong; Park, Junyong
Abstract: Two‐photon interference lithography with an elastomeric phase grating that allows spontaneous conformal contact to the photoresist can be used to fabricate practical‐scale, 3D photonic crystals through a single exposure. In principle, the unit cell symmetry and fill factor of the 3D periodic nanostructures produced using this technique are strongly depend on the structural parameters of the phase grating. However, theoretical approaches to derive the optimal parameters of the phase grating for realizing high‐definition 3D nanostructures are still lacking. Here, the change in the Talbot interference pattern is systematically predicted with the relief height of the phase grating under the conditions in which two‐photon interference lithography is performed through optical simulations. The collective set of results reveals the design error of the relief height of the phase grating, as inferred by the scalar approximation thus far, and presents the optimal condition that satisfies the π‐phase shift inferred by the full‐vectorial numerical solution. Abstract : Optical 3D nanolithography using Talbot interference generated from conformable phase gratings is widely used in the experimental realization of numerous emerging materials including 3D photonic crystals. A new theoretical approach on optimizing the structural parameters of the phase grating is presented here to fabricate high‐quality 3D nanostructures.